Pengaruh ROA dan ROE Terhadap NPF pada Bank Umum Syariah Periode 2020-2022 - Rachmania Rachmania; Alfina Muizana (CV. Ulil Albab Corp, 2024)
This research to determine the effect of ROA and ROE Ratios on NPF Ratio Ten Islamic Commercial Banks satisfy the requirements out of the total population of Islamic Commercial Banks in this study. The IBM SPSS Statistics 26 program is used in this study's quantitative methodologies. The findings indicated that NPF was not impacted in any way by ROA or ROE. Together, ROA and ROE have a simultaneous impact on the NPF Ratio. The research's findings to show that there is a moderate association between ROA and ROE and the NPF variable, with a R-value of 0.505.